2014
DOI: 10.1002/ebch.1978
|View full text |Cite
|
Sign up to set email alerts
|

Combined and alternating paracetamol and ibuprofen therapy for febrile children

Abstract: There is some evidence that both alternating and combined antipyretic therapy may be more effective at reducing temperatures than monotherapy alone. However, the evidence for improvements in measures of child discomfort remains inconclusive. There is insufficient evidence to know which of combined or alternating therapy might be more beneficial.Future research needs to measure child discomfort using standardized tools, and assess the safety of combined and alternating antipyretic therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
39
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(44 citation statements)
references
References 43 publications
1
39
0
1
Order By: Relevance
“…This needs to be reviewed carefully as data on safety and efficacy of alternating combined therapy in children with pain is lacking [28,30]. A systematic review concluded that the safety and efficacy of the combination of ibuprofen and paracetamol in fever remains obscure [31] and there may be an additional risk for medication errors [32].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This needs to be reviewed carefully as data on safety and efficacy of alternating combined therapy in children with pain is lacking [28,30]. A systematic review concluded that the safety and efficacy of the combination of ibuprofen and paracetamol in fever remains obscure [31] and there may be an additional risk for medication errors [32].…”
Section: Discussionmentioning
confidence: 99%
“…Paediatric studies on newer, medium potent opioids such as tapentadol are ongoing within the frame of a paediatric investigation plan (PIP) and results may become available in the near future [39,40]. Also more data regarding the benefits and risks of paracetamol, ibuprofen and its combinations became available and may influence practice [31]. Therefore, our data form an excellent basis to evaluate the impact of these latest regulatory developments and to compare the effectiveness of changes in guidelines and recommendations.…”
Section: Discussionmentioning
confidence: 99%
“…In study by Kokki the effect of antipyretic paracetamol, ibuprofen and ketoprofen were compared with each other to reduce the child's temperature and showed that ketoprofen in the symptomatic treatment of fever in children is more effective than other drugs [18]. Wong concluded that the combination therapy compared to alternative antipyretic was more effective in reducing the temperature [19]. In a study by Smith observed that, despite of acetaminophen and ibuprofen alternative therapies for the treatment of pain in children, there is no evidence of the appropriateness and effectiveness of treatment.…”
Section: Discussionmentioning
confidence: 99%
“…To date, there is limited but promising evidence to support the practice of combining acetaminophen and ibuprofen for pain treatment in children. [20][21][22][23][24] As noted by others, there remains a need for large-scale studies on both the efficacy and safety of this combination for the treatment of pain. 20 When asked to choose their preferred oral analgesic, respondents showed a strong preference for ibuprofen over acetaminophen.…”
Section: Discussionmentioning
confidence: 99%